Функціональний нирковий резерв при хронічних токсичних нефропатіях - Гоженко, А.І.; Котюжинська, С.Г.; Бурлака, Н.І.; Слученко, О.М. (Актуальні проблеми транспортної медицини, 2007)
В условиях водной и солевой нагрузки были проведены исследования действительного функционального состояния почек крыс с учетом их резервных возможностей при нефропатии сулемы через 7діб и через 20 суток. Установлено, что рост скорости клубочковой фильтрации за счет включения функционального почечного резерва является одним из основных способов активизации функциональных возможностей почек при токсичных нефропатиях, которые являются основой фазы компенсации и маскирует уменьшение массы функциональных нефронов и нарушение почечных функций. The research of real functional condition of rat's kidneys were carried out in the conditions of water and saline loads, taking their reserve possibilities into consideration, against a background of toxic nephropathy on 7 and 20 days. It has been established, that increase of glomerular velocity filtrations through inclusion of functional kidney reserve is one of basic methods of increase of activity of functional possibilities of kidneys against a background of toxic nephropathy that is a basis of phase of compensation and camouflage a decrease of number of functional nephrons and an injury of renal functions.